Peran Perempuan dalam Membantu Perekonomian Keluarga di Desa Sambirejo Timur Kabupaten Deli Serdang - Arzetty Meutya Noersy; Suheri Harahap; Ahmed Fernanda Desky (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The family, the smallest unit in society, consists of father, mother and children. In general, a family consists of people who are related by blood or marriage, although they do not always share a roof (house, dining table, food, money, even feelings) and this is an element to characterize a gathering as a family. Because she is responsible for her children, women in a family have responsibilities in the domestic realm. It seems that the role of women in East Sambirejo Village has changed, namely that women are prioritized to work outside the home so that they have limitations in caring for children. This is what is of interest to researchers in conducting research, namely with the aim of studying more deeply the role of women in earning a living in the public sector. This research method uses qualitative research, a descriptive approach with a total of 5 informants. Data collection techniques use interviews, observation and documentation. The results of this research show that the wife's role as the family breadwinner is due to poverty. As experts in liberal feminist theory, J. S. Mill and Harriet Taylor-Mill (husband and wife), argue that equality between men and women has been achieved, that women must have the same civil rights as men and equal access to education, economic participation, and other opportunities. This is stated because, in both views, individuals must be given the freedom to pursue their goals, as long as they do not interfere with each other in the process of achieving their goals. However, from a religious perspective or from an Islamic perspective, women are not required to earn a living, so everything that has been explained in Islamic law is felt to be able to bring about benefits for its people. Relating to the husband's maintenance obligations towards the family. as Allah says in surah Al-Baqarah 2: verse 233. based on analysis of social construction theory which states that the role of the wife as the family breadwinner is the result of human construction. The first three stages of social construction in the people of East Sambirejo Village are externalization or adjustment to the socio-cultural world by adjusting the wife to her family's economy, changes in habits in East Sambirejo Village, and understanding of religion, especially in verses of the Al-Qur'an'an surah. Al-Baqarah 2:233 regarding the husband's obligation to support his family. Second, (objectivity) self-interaction with the social and cultural world. In society, the wife is expected to be the breadwinner of the family all the time, and she does so with self-awareness to help support the family. Third, examples of self-identification with the sociocultural world (internalization). In this process, the wife plays the role of breadwinner for the family in East Sambirejo Village with the aim of supporting the family's economy (economic factor).